An Argument in Defense of Voluntary Euthanasia - حسین اترک (Journal of Philosophical Investigations, 2019)
One of the most challenging issues in medical ethics is a permission or prohibition of euthanasia. Is a patient with an incurable disease who has lots of pain permitted to kill oneself or ask others to do that? The main reason advanced by the opponents is the absolute prohibition of murder. Accordingly, the meaning of murder plays a key role in determining the moral judgment of euthanasia. The aim of this paper is to confirm the role of intention in moral judgment of euthanasia and eliminate the name of unjust murder from voluntary euthanasia. The Intention of an agent determines the name of the act and whether it is right or wrong.  An important point that dose not taken into account in the definitions of murder, killing as well as their ethical judgment is considering the attributes of being unjust and forcible. Killing a human being is neither intrinsically good nor bad, but its ethical judgment depends on the way that happens, i.e. just or unjust. Every killing is neither bad nor unethical except unjust one which is both bad and unethical. The attribute of “unjust” has been mentioned in the definition of murder in Islamic jurisprudence, law, traditions, and Quran. Owing to this argument, on one hand, it is true to state that voluntary euthanasia is not unjust and forcible murder (the test of correct negation), and on the other hand, it is not true to say that voluntary euthanasia is unjust and forcible murder (the test of incorrect predication). It can be concluded that voluntary euthanasia is an independent title other than unjust murder and does not have its judgment.